2015
DOI: 10.1038/jid.2015.184
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Impact of Two Keratin Mutations Causing Epidermolysis Bullosa Simplex on Keratinocyte Adhesion and Stiffness

Abstract: Keratin filaments constitute the major component of the epidermal cytoskeleton from heterodimers of type I and type II keratin subunits. Missense mutations in keratin 5 or keratin 14, highly expressed in the basal epidermis, cause the severe skin blistering disease epidermolysis bullosa simplex (EBS) in humans by rendering the keratin cytoskeleton sensitive to mechanical stress; yet, the mechanisms by which individual mutations cause cell fragility are incompletely understood. Here, we compared the K14p.Arg125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 42 publications
5
65
1
Order By: Relevance
“…Those observations were recently highlighted by findings of increased caspase 8 both in lesional and non-lesional areas in EBS patients 24 which suggests the mutations have additional consequences beyond a simple break of cells. Moreover, evidence from the Magin lab supports the notion that expression of the R125P K14 alone makes cells mechanically weaker than cells lacking keratins altogether 25 . Furthermore, data from Marceau lab suggest that in internal epithelia, keratins 8/18 contribute to cell stiffness via cortical actin, by activation of the ROCK signaling pathway 26 .…”
Section: Keratins Mechanical Is Not Mechanisticmentioning
confidence: 81%
“…Those observations were recently highlighted by findings of increased caspase 8 both in lesional and non-lesional areas in EBS patients 24 which suggests the mutations have additional consequences beyond a simple break of cells. Moreover, evidence from the Magin lab supports the notion that expression of the R125P K14 alone makes cells mechanically weaker than cells lacking keratins altogether 25 . Furthermore, data from Marceau lab suggest that in internal epithelia, keratins 8/18 contribute to cell stiffness via cortical actin, by activation of the ROCK signaling pathway 26 .…”
Section: Keratins Mechanical Is Not Mechanisticmentioning
confidence: 81%
“…Of note, even mutations causing severe disease do not prevent formation of long keratin intermediate filaments (KIFs) in vitro (Herrmann et al 2002), suggesting that mutations and physical stress act at the level of keratin bundling, network organization, dynamics, or by affecting association with other proteins. Indeed, the most frequent KRT14 Arg125 mutation compromises desmosome adhesion (Russell et al 2004;Homberg et al 2015).…”
Section: Human Disease and Mouse Modelsmentioning
confidence: 99%
“…The resulting perinuclear keratin reorganization affects the viscoelasticity of metastatic cancer cells and promotes tumor invasion (Beil et al 2003). Mechanically stretching of keratinocytes expressing EBS-like keratin mutations triggered a progressive disassembly of desmosomes and weakened intercellular adhesion (Russell et al 2004;Homberg et al 2015). Thus, keratin reorganization on posttranslational modifications might contribute to the invasive properties of metastatic tumor cells and to altered adhesion in skin disorders (Beil et al 2003;Russell et al 2004;Homberg et al 2015;Loschke et al 2016).…”
Section: Impact Of Mechanical Stretch On the Desmosome -Keratin Complexmentioning
confidence: 99%
“…The cytoskeleton is recognised as the determinant of cell mechanical properties and the actin network has been evidenced as the key player due to its involvement in migration, differentiation and signalling pathways associated with the transduction of mechanical information [Welch et al, 1997;Ingber, 2006;Asparuhova et al, 2009;Wang et al, 2009;Roca-Cusachs et al, 2013;Blanchoin et al, 2014]. However, it has been shown that intermediate filaments (IFs) also play a role in these cellular processes [Eckes et al, 1998;Ivaska et al, 2007;Alam et al, 2011;Homberg et al, 2015;Leduc and Etienne-Manneville, 2017] and that they participate in cell mechanics properties [Wang and Stamenović, 2000;Guo et al, 2013;Seltmann et al, 2013;Ramms et al 2013;Charrier and Janmey, 2016]. IFs are a class of proteins with a tripartite structure: hydrophilic head and tail, and an alpha-helical domain composed of hydrophilic and hydrophobic amino acids in the central position [Weber and Geisler, 1985;Fuchs and Weber, 1994].…”
Section: Introductionmentioning
confidence: 99%